Kompleks Islam Putrajaya - Zaki, Muhammad Izham; Rahiman, Mohammad Afiq; Mohd Zamri, Mohammad Iirfan (2024)
Putrajaya Islamic Complex was first built in October 2011 in Presint 3, Putrajaya. The construction was completed in August 2016 and commenced operations on 1 December 2016. The office block was built on a 2.28-hectare site. The Putrajaya Islamic Complex, which is motivated by modern Islamic architecture, consists of four blocks namely Blocks A, B,C and D. This complex house nine religious agencies under the portfolio of Religious Affairs, Prime Minister’s Department. Blocks A,C and D are connected by a bridge that is on the second floor in each block. The building also has an underground auditorium and can accommodate about 773 people. The Putrajaya Islamic Complex was inaugurated on 18 July 2017 by thew Prime Minister of Malaysia, Najib Razak. Putrajaya Islamic Complex features Islamic architecture and the latest technology. The arch on the roof shows the beauty of geometry featuring curves shaped like “roof weaving”.